EKSPLORASI PERAN MAHASISWA PGSD DALAM MENINGKATKAN LITERASI DAN NUMERASI DI SEKOLAH DASAR - Ulin Husnul Khotimah; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to explore the strategic role of students from the Primary School Teacher Education Study Program (PGSD) in improving students' literacy and numeracy skills at the elementary school level. The urgency of this research is based on Indonesia's low ranking in the 2022 PISA survey, where literacy scores in reading (355 points) and mathematics (379 points) are far below the international average. Apart from that, the results of observations at SDN 13/I Muara Bulian show low interest in independent reading, dependence on teacher instructions, and students' fear of mathematics which is considered a "forest of formulas. The method used in this research is a qualitative descriptive approach with literature study. Data was collected through reviews of scientific articles, textbooks and relevant theories regarding the role of PGSD students as agents of change in the digital era. The results of the research show that PGSD students have a central role as innovators and learning facilitators who are able to integrate educational technology to develop students' digital literacy. The role of students. includes developing creative learning strategies to overcome students' obstacles in understanding contextual logic questions and text inference.